WOMen profEssioNal developmenT oUtcome Metrics in Academic Emergency Medicine: Results from the WOMENTUM Modified Delphi Study - Jennifer S. Love; Amy J. Zeidan; Utsha G. Khatri; Margaret E. Samuels-Kalow; Angela M. Mills; Cindy H. Hsu (Western Journal of Emergency Medicine, 2022)
Introduction: To address persistent gender inequities in academic medicine, women professional development groups (PDG) have been developed to support the advancement of women in medicine. While these programs have shown promising outcomes, long-term evaluative metrics do not currently exist. The objective of this study was to establish metrics to assess women’s PDGs. Methods: This was a modified Delphi study that included an expert panel of current and past emergency department (ED) chairs and Academy for Women in Academic Emergency Medicine (AWAEM) presidents. The panel completed three iterative surveys to develop and rank metrics to assess women PDGs. Metrics established by the expert panel were also distributed for member-checking to women EM faculty. Results: The expert panel ranked 11 metrics with high to moderate consensus ranking with three metrics receiving greater than 90% consensus: gender equity strategy and plan; recruitment; and compensation. Members ranked 12 metrics with high consensus with three metrics receiving greater than 90% consensus: gender equity strategy and plan; compensation; and gender equity in promotion rates among faculty. Participants emphasized that departments should be responsible for leading gender equity efforts with PDGs providing a supportive role. Conclusion: In this study, we identified metrics that can be used to assess academic EDs’ gender equity initiatives and the advisory efforts of a departmental women’s PDG. These metrics can be tailored to individual departmental/institutional needs, as well as to a PDG’s mission. Importantly, PDGs can use metrics to develop and assess programming, acknowledging that many metrics are the responsibility of the department rather than the PDG.